Equity in Urban Climate Change Adaptation Planning: A Review of Research - Swanson, Kayleigh (2021)
A growing number of cities are preparing for climate change by developing adaptation plans, but little is known about how these plans and their implementation affect the vulnerability of groups experiencing various forms of underlying social inequity. This review synthesizes research exploring the justice and equity issues inherent in climate change adaptation planning to lay the foundation for critical assessment of climate action plans from an equity perspective. The findings presented illuminate the ways in which inequity in adaptation planning favours certain privileged groups while simultaneously denying representation and resources to marginalized communities. The review reveals the specific ways inequity is experienced by disadvantaged groups in the context of climate change and begins to unpack the relationship between social inequity, vulnerability, and adaptation planning. This information provides the necessary background for future research that examines whether, and to what extent, urban adaptation plans prioritize social vulnerability relative to economic and environmental imperatives.